STRATEGI PENINGKATAN PRODUKTIVITAS KARYAWAN CV. NISA CATERING SANGATTA - Kusumah, Angga (Tinta Nusantara 2018 Vol.1, 2024)
CV. Nisa Catering Sangatta was established in Sangatta on January 7, 2019 by Notary Redi Allo Padang, S.H., M.Kn. The author wants to research how to improve employee productivity strategies at CV. Nisa Catering Sangatta. The main focus of this study is to identify factors that influence employee productivity at CV. Nisa Catering Sangatta. This study uses a qualitative method. In this study, data collection techniques used observation and interviews. The data obtained were then processed and then developed into certain relationship patterns. In this study, the data sources used were primary data sources and secondary data. The results of the study explain that the strategy used at CV. Nisa Catering Sangatta implements a focus on improving skills through routine training, providing incentives and rewards to motivate employees, encouraging open communication between management and employees to ensure that any problems or obstacles in work can be resolved quickly and adopting a digital management system to manage work schedules, orders, and inventory. This study reveals that the company also creates a conducive work environment with adequate facilities. These steps are designed to provide the motivation and support necessary for employees to work more efficiently and productively